A conceptual model of students' reflective practice for the development of employability competences, supported by an online learning platform. Issue 3 (27th January 2022) - Heymann, Perry; Bastiaens, Ellen; Jansen, Anne; van Rosmalen, Peter; Beausaert, Simon
Abstract : Purpose: In a fast evolving labour market, higher education graduates need to develop employability competences. Key in becoming employable is the ability to reflect on learning experiences, both within a curriculum as well as extra-curricular and work placements. This paper wants to conceptualise how an online learning platform might entail a reflective practice that systematically supports students in reflecting on their learning experiences. Design/methodology/approach: When studying online learning platforms for developing students' employability competences, it became clear that the effectiveness of the platform depends on how the platform guides students' reflective practice. In turn, the authors studied which features (tools, services and resources) of the online learning platform are guiding the reflective practice. Findings: This resulted in the introduction of an online learning platform, containing a comprehensive set of online learning tools and services, which supports students' reflective practice and, in turn, their employability competences. The online platform facilitates both feedback from curricular and work-related learning experiences and can be used as a start by students for showcasing their employability competences. The reflective practice consists of a recurrent, systematic process of reflection, containing various phases: become aware, analyse current state, draft and plan a solution, take action and, finally, reflect in and on action. Research limitations/implications: Future research revolves around studying the features of online learning platforms and their role in fostering students' reflection and employability competences. Practical implications: The conceptual model provides concrete indicators on how to implement online learning platforms for supporting students' reflection and employability competences. Originality/value: This is the first article that analyses an online learning platform that guides students' reflective practice and fosters their employability competences. The authors provide concrete suggestions on how to model the online platform, building further on reflective practice theory.